Pengaruh Experiential Marketing dan Physical Evidence terhadap Loyalitas Konsumen Kafe Tea Break Kota Bima - Ahmad Jadari; Sri Ernawati (LANCAH: Jurnal Inovasi dan Tren, 2023)
This research was conducted with the aim of knowing and analyzing the effect of experiential marketing and physical evidence on consumer loyalty at the Bima City Tea Break Cafe. This type of research is associative. The research instrument used in this study was a questionnaire with a Likert scale. The population used in this research is all Tea Break consumers in Bima City whose exact number is not known, so the number of samples used is 50 people. The sampling technique used was a non-random sampling technique with a purposive sampling method. Data collection techniques used are observation, questionnaires or questionnaires and literature study. Data analysis techniques used validity test, reliability test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), followed by multiple linear regression analysis, multiple correlation coefficients, t test and f test. The results showed that Experiential marketing and physical evidence did not have a significant effect simultaneously on the Bima City Tea Break Café.